Cryopreservation of Hydractinia symbiolongicarpus Sperm to Support Community-Based Repository Development for Preservation of Genetic Resources - Aidan L. Huene; Jack C. Koch; Lucía Arregui; Yue Liu; Matthew L. Nicotra; Virginia M. Weis; Terrence R. Tiersch (Animals, 2022)
Hydractinia symbiolongicarpus is an emerging model organism in which cutting-edge genomic tools and resources are being developed for use in a growing number of research fields. One limitation of this model system is the lack of long-term storage for genetic resources. The goal of this study was to establish a generalizable cryopreservation approach for Hydractinia that would support future repository development for other cnidarian species. Specific objectives were to: (1) characterize basic parameters related to sperm quality; (2) develop a generalizable approach for sperm collection; (3) assess the feasibility of in vitro fertilization (IVF) with sperm after refrigerated storage; (4) assess the feasibility of IVF with sperm cryopreserved with various sperm concentrations; (5) evaluate feasibility of cryopreservation with various freezing conditions, and (6) explore the feasibility of cryopreservation by use of a 3-D printed open-hardware (CryoKit) device. Animal husbandry and sperm collection were facilitated by use of 3-D printed open hardware. Hydractinia sperm at a concentration of 2 × 107 cells/mL stored at 4 °C for 6 d were able to achieve 50% fertilization rate. It appeared that relatively higher sperm concentration (>5 × 107 cells/mL) for cryopreservation could promote fertilization. A fertilization rate of 41–69% was observed using sperm equilibrated with 5, 10, or 15% (v/v) cryoprotectant (dimethyl sulfoxide or methanol) for 20 min, cooled at a rate of 5, 10, or 20 °C/min from 4 °C to −80 °C, at a cell concentration of 108/mL, in 0.25 mL French straws. Samples cryopreserved with the CryoKit produced a fertilization rate of 72–82%. Establishing repository capabilities for the Hydractinia research community will be essential for future development, maintenance, protection, and distribution of genetic resources. More broadly, these generalizable approaches can be used as a model to develop germplasm repositories for other cnidarian species.